Development of learning media for the female reproductive system based on augmented reality - Devy Kurnia Ramadhani; Dian Trisnasari; Agus Sugiono (Poltekkes Kemenkes Yogyakarta, 2024)
Midwifery practice has contributed to the reduction of maternal and child mortality by applying biomedical sciences, one of which is anatomy. Anatomy education learning usually uses cadavers, models, and books, but they are considered less effective. This study aims to develop applications based on augmented reality for learning media on the female reproductive system. This research was a research & development research and uses a waterfall application development model to get applications for learning media. The research and development steps carried out in the research included: needs analysis, design and implementation. The research was conducted at the Department of Midwifery, Poltekkes Kemenkes Yogyakarta in 2021. Based on a needs analysis, interactive learning media were developed, one of which was using Augmented Reality technology. The development design uses Unidentified Modelling Language (UML) i.e. use case diagram, class diagram, and sequence diagram. Development implementation in the form of markers, 3D animation, and application implementation. The Augmented Reality application for the Female Reproductive System can be used for learning and requires usability testing.